Beyond Sectarianism: The Missional Church in a Post-Christendom Society - Nikolajsen, Jeppe Bach (Missiology, 2013)
An increasing number of theologians assert that the Western world has moved from a Christendom era to a post-Christendom era. In relation to this, this article discusses the charge of sectarianism. The article argues that the task that lies before the church in the Western world in not to bypass its distinctiveness with accusations of sectarianism, but to recapitulate an understanding of its own distinctiveness that should be seen as a precondition for its engagement in society. Such an ecclesiological position holds, it is asserted, important potential for an understanding of the role of a missional church in a post-Christendom society.